HOW WORKPLACE CONDITION AFFECTS HEALTHCARE WORKERS: ASSESSMENT AT TERTIARY HOSPITALS - Shaik Farid AW; Ahmad Rasdan lsmail; Rohayu O (Malaysian Journal of Public Health Medicine, 2020)
Complaint of pain due to work related musculoskeletal disorder at workplace is nothing new. Nevertheless, in Malaysia, the data leading to this is near to none, when healthcare industry is concerned. The purpose of this article is to evaluate the current physical condition at red zone of accident and emergency department at selected hospitals and has the current condition contribute to the work-related musculoskeletal disorder among healthcare personnel. The study is conducted at five red zones of accident and emergency department of Malaysia tertiary hospitals. Before conducting the study, ethical approval has been obtained from ethical committee of Kementerian Kesihatan Malaysia. Method used in this study is workplace assessment, which allows first-hand experienced to determine and evaluate the real condition of red zone at selected hospitals. Duration of twelve months is required to complete the assessment. During the workplace assessment, the lighting at red zone (focusing on bed area), the bed space, arrangement of equipment and height of monitors are observed, measured and recorded. Result show, every red zone is unique with its own layout and design. There is no standardization among all the red zones involved. Existing guideline for physical condition of red zone of accident and emergency does not exist. Thus, relationship between physical condition of existing red zone and whether it causes work related musculoskeletal disorder must be discussed in length.